2022
DOI: 10.1055/a-1938-6042
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cerclage vs. Pessary in Women with a Short Cervix on Ultrasound

Abstract: Purpose: In the present study we sought to compare the efficacy of cervical pessary to that of cerclage in terms of reducing preterm birth rates among women with a short (<25 mm) and ultra-short (<15 and <10 mm) cervix during the ultrasonographic second trimester assessment. Method: We retrospectively searched the hospital records for singleton pregnancies diagnosed with cervical insufficiency during the second trimester of pregnancy. The McDonald cerclage was used in all women with the use of a 5mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…These studies suggested that sonographic cervical shortening is a marker for CI. 7 , 8 However, only 27% of the women with short cervix in the preterm prediction research gave birth before 37 weeks, and less than 18% of women gave birth before 35 weeks. 9 CL exhibited little predictive efficacy as a single indicator, with extremely short cervix less than 15 mm only conferring a 50% chance of delivery prior to 33 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggested that sonographic cervical shortening is a marker for CI. 7 , 8 However, only 27% of the women with short cervix in the preterm prediction research gave birth before 37 weeks, and less than 18% of women gave birth before 35 weeks. 9 CL exhibited little predictive efficacy as a single indicator, with extremely short cervix less than 15 mm only conferring a 50% chance of delivery prior to 33 weeks.…”
Section: Introductionmentioning
confidence: 99%